PERBEDAAN INTERVENSI CORE STABILITY DAN SIT TO STAND TERHADAP KESEIMBANGAN DINAMIS PADA ANAK CEREBRAL PALSY DIPLEGIA DI KLINIK TUMBUH KEMBANG ANAK RS SENTRA MEDIKA CIKARANG - Kirana Dewanty; Helmi Putra Suteja; Nabila Salsabillah Warasti (Cahaya Ilmu Bangsa Institute, 2025)
Background: Children with diplegia cerebral palsy often experience dynamic balance disorders due to motor limitations. Effective interventions are needed to improve dynamic balance and reduce the risk of falls. Objective: This study aims to compare the effectiveness of Core Stability and Sit To Stand interventions in improving dynamic balance in children with diplegia cerebral palsy. Methods: This study used a pseudo-experimental design with pre-test and post-test in two treatment groups. A total of 24 children with cerebral palsy diplegia were randomly divided into two groups, namely the Core Stability group and the Sit To Stand group. The intervention was carried out for 4 weeks with a frequency of 2 times per week. Results: The results of the study using SPSS with significant results with a result of 0.00 where the p value is 0.05 which means there is a significant difference in the two groups. Conclusion: Core Stability is more effective in improving dynamic balance compared to Sit To Stand in children with cerebral palsy diplegia. This intervention is recommended as part of a rehabilitation program for children with this condition.